Potensi Daur Ulang Sampah Domestik Di Wilayah Pengembangan I Kota Pekanbaru - Putri, Dini Riskiana; Yenie, Elvi; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This study aims to determine the data generation, composition, physical and chemical characteristics of domestic waste and the potential for recycling in the Development Area I of Pekanbaru City based on the level of income levels of the High Income, Medium Income and Low Income. The data generated can be used for planning and development for waste management systems. Determination of waste generation is done based on SNI 19-3964-1994 method. The results showed that Sukajadi District's solid waste generation was in the weight unit of 0.407 kg / o / day and a volume unit of 2.86 l / o / day, Senapelan District in the weight unit of 0.383 kg / o / day and a volume unit of 2.64 l / o / day, Pekanbaru City District in units of weight 0.396 kg / o / day and volume units 2.61 l / o / h, Lima Puluh District in weight units 0.373 kg / o / day and volume units 2.13 l / o / day and Sail District in weight units 0.383 kg / o / day and volume unit 2.53 l / o / day. Waste composition in Pekanbaru City Development Area I is dominated by organic waste by 48%. Physical characteristics of brupa gravity specific gravity is 0.09 kg / l and compaction factor is 1.07 l / day. Chemical characteristics for water content are 35.80%, volatile content is 58.73%, ash content is 1.64% and fixed carbon is 3.83%. potential for waste recycling Domestic Development Region I Pekanbaru City is divided into two types of recycling, namely composting final product at 462.738 kg / day and Recyclable at 131.08 kg / day. Keywords: domestic waste, waste generation, composition of waste, potential for waste recycling